Family, religion, and identity in the Pakistani diaspora : a case study of young Pakistani men in Dublin and Boston - Considine, Craig (Trinity College (Dublin, Ireland). Department of Sociology, 2014)
In recent years, Western countries have received Pakistanis as religious fanatics and detrimental to national as well as international safety and politics. Pakistani communities in diaspora have, in turn, received negative attention for controversies surrounding religious activities and a noted lack of integration into host societies. In Ireland and the US, Pakistanis are faced with different challenges due to the migration histories of Pakistanis into these countries, the role of religion in Irish and American societies, and how ideas of the ‘nation’ have affected individual migrant lives. While the Pakistani diaspora is well researched as one of the largest diasporic communities in the world, little is known about these populations in Dublin and Boston. This study fills the gap in literature by examining the experiences of young Pakistani men through their engagement with family, religion, and identity. In comparing the experiences of young Pakistani men in Dublin and Boston, this study explores the heterogeneity of the Pakistani diaspora, an issue that has been largely overlooked in diaspora studies. This study looks at how young Pakistani men between the ages of 18 and 35 position themselves in relation to ethnicity, religion, and nationality. By examining the lived experiences of first- and second-generation Pakistani Muslim as well as non-Muslim men, the thesis considers migrant generational differences, the impact of religious affiliations, as well as the development of individual identities in the Irish and American contexts. The study draws upon diaspora theory, specifically the concepts of boundary maintenance, homeland, and cultural borderland, to look at how these men negotiate the native and host cultures. To investigate the heterogeneity of the Pakistani diaspora, the research design sampled individuals from different sub-ethnic groups, religions, sexualities, and socioeconomic backgrounds. A series of semi-structured interviews, focus groups, and participant observation notes were used to account for the individuals’ lived experiences.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin